(untitled) (ETIMA, 2024)
The paper deals with the types of hydrogen production, methods for its storage and transport and possibilities of end use of hydrogen. The basics of hydrogen economy are briefly describing and then the SWOT analysis of hydrogen economy is performed. The strengths, weaknesses, opportunities, and threats of hydrogen economy are summarized in the SWOT analysis. Based on that analysis, the biggest problems, and threats with possibil-ities of solving those problems are summarized. SWOT analysis considers aspect of hy-drogen economy e.g. from energy demands, financial difficulty, safety, and awareness about hydrogen. Conclusions involve suggestion how to avoid above-mentioned aware-ness, and how could rise hydrogen utilization.